2022
DOI: 10.4103/ijem.ijem_164_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Addison’s Disease in a Tertiary Care Institute, Southern India – The Changing Landscape

Abstract: Aims and Objectives: Clinical, biochemical, and radiological profiles of Addison’s disease and to assess the various etiological spectrum of primary adrenal insufficiency (PAI) in adults. Materials and Methods: A retrospective cohort study was carried out in the Department of Endocrinology, Madurai Medical College, Madurai between January 2014 and January 2021 over a 7-year period. Inclusion Criteria: All the patients with clinical symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…73 However, a retrospective, cohort study from 2022 concerning Southern India included 36 patients with PAI between 2014 and 2021 (female to male ratio of 19:17, median age at diagnosis of 35 years) and 87% of patients had nontuberculosis etiology which might show a shift of etiology even in countries where infectious AD was found to be more frequent than autoimmune AD. 74 Another retrospective Indian study identified 15 cases with adrenal incidentalomas, and 11/15 of them were adrenal histoplasmosis (82% males, 100% HIV negative); 4 individuals developed AD; anti-fungal therapy with itraconazole and/or amphotericin B was added to endocrine approach. 75 A single-center, retrospective study (Eastern India) between 2015 and 2019 included 9 cases of adrenal histoplasmosis; 77% of them had clinically suggestive features of AD; 100% had bilateral involvement; anti-fungal medication was added to standard AD care; the outcome showed that one (1/9) patient died, the response to medication was favorable without AD recovery (8/9) 76 (Table 4).…”
Section: Management and Outcome In Addison's Disease Etiology-based S...mentioning
confidence: 99%
“…73 However, a retrospective, cohort study from 2022 concerning Southern India included 36 patients with PAI between 2014 and 2021 (female to male ratio of 19:17, median age at diagnosis of 35 years) and 87% of patients had nontuberculosis etiology which might show a shift of etiology even in countries where infectious AD was found to be more frequent than autoimmune AD. 74 Another retrospective Indian study identified 15 cases with adrenal incidentalomas, and 11/15 of them were adrenal histoplasmosis (82% males, 100% HIV negative); 4 individuals developed AD; anti-fungal therapy with itraconazole and/or amphotericin B was added to endocrine approach. 75 A single-center, retrospective study (Eastern India) between 2015 and 2019 included 9 cases of adrenal histoplasmosis; 77% of them had clinically suggestive features of AD; 100% had bilateral involvement; anti-fungal medication was added to standard AD care; the outcome showed that one (1/9) patient died, the response to medication was favorable without AD recovery (8/9) 76 (Table 4).…”
Section: Management and Outcome In Addison's Disease Etiology-based S...mentioning
confidence: 99%
“…The disorder in the secretion of adrenaline leads to anxiety, lowering immunity and hypertension. The adrenaline deficiency in the human body causes Addison’s disease and excess adrenaline leads to pheochromocytoma . The regulation of adrenaline concentration in the human body is essential for a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…The adrenaline deficiency in the human body causes Addison's disease and excess adrenaline leads to pheochromocytoma. 2 The regulation of adrenaline concentration in the human body is essential for a healthy lifestyle. Therefore, its detection has importance from medical and healthcare points of view.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the present case, alopecia preceded hyperthyroidism by three years. [ 3 ] Hence, vigilant follow-up is required in all autoimmune disorders.…”
mentioning
confidence: 99%